Inefisiensi Pelayanan Publik di Indonesia pada Era Digital dan Implikasinya terhadap Pencapaian Tujuan Organisasi - Sri Yuliyanty Mozin; Alfiyah Agussalim; Lia Kristiyanti Lipabundu; Dinaty Nur Annisa Sy. Panigoro; Rinjani Hurratun Idrisah; Syalwa Reyhana Pasilia; A'yunin Ibrahim; Prasetyo Otuh (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study examines public service inefficiency in Indonesia during the digital era and its implications for achieving governmental organizational goals. Digital transformation through the implementation of e-government and technology-based public services is expected to improve effectiveness, transparency, and service quality. However, several challenges remain, including weak system integration, rigid and hierarchical bureaucratic structures, limited human resource competencies, lack of sustainable service innovation, and inadequate supervision mechanisms. This research employs a literature study method with a descriptive-qualitative approach by analyzing various academic sources such as journals, books, and relevant policy documents. The findings indicate that digitalization has not fully reduced inefficiency due to structural barriers, organizational behavior issues, and the lack of an adaptive work culture. Therefore, strengthening human resource competencies, improving digital system integration, encouraging continuous service innovation, and enhancing supervision are necessary to ensure that digital public services effectively support the achievement of organizational goals.